Financial costs of sprawl in Malaysia: Conceptual framework - Osman, Shahriza; Nawawi, Abdul Hadi; Abdullah, Jamalunlaili (2008)
This is a conceptual paper on the financial costs of sprawl.There are varying opinions about the qualitative costs and benefits of sprawl, but the quantitative studies suggest that sprawl is more costly, both monetized and non-monetized terms.Sprawling development results in higher government costs.The primary concern about sprawl development in its outcome, that is cost.It has been a problematic aspect of metropolitan growth and development all around the world. Much has been studied on the social, economic and environment cost but financial cost received limited scholarly attention.Thus, financial cost will include infrastructure, transportation, capital, operating and also resource depletion cost. Analysis on cost of sprawl (Burchell 1998) found that savings of $420 billion in real estate development costs can be achieve through more compact development.Savings are a by product of more compact development cities can save developer time and money through policies that encourage compact, mixed-use growth.The financial cost need to be measured in terms of efficiency in operating, financing and investment decisions in the urban services provided.These costs need to be reconciled to local government and private spending and expenditures based on landuse patterns of a region.The implications include both positive and negative, and much effort need to be intensified by all players in the urban development.The ability to access, measure and monitor sprawl depend on the availability of relevant, accurate reliable data. This paper will focus on the financial cost of sprawl, which has limited scholarly attention in Malaysia.